Unlocking the Burp Reflex: A Review of Retrograde Cricopharyngeal Dysfunction - Chludek, Aleksandra; Dańda, Karol; Chobot, Barbara; Wachowska, Marta; Chmielowiec, Julia; Czyżewicz, Zuzanna; Dworak, Kinga; Trędota, Natalia; Posid, Dominika; Lewczuk, Michał (Quality in Sport, 2026)
Introduction: The aim of this review is to synthesize current evidence on retrograde cricopharyngeal dysfunction in light of the rapidly expanding literature, summarizing contemporary knowledge on its pathophysiology, diagnosis, and management. Additionally, this study highlights challenges related to access to diagnostic and therapeutic services and underscores the significant impact of the condition on patients’ quality of life. Materials and methods: A comprehensive review of the literature was conducted using the PubMed and Google Scholar databases using keywords: „retrograde cricopharyngeal dysfunction ”, „ R-CPD ”, „abelchia ”, „ inability to belch ”, „ inability to burp”, „upper esophageal sphincter”, „UES”. Citations were also screened in each article for additional sources. Conclusions: Retrograde cricopharyngeal dysfunction (R-CPD) is an underrecognized condition with a characteristic symptom profile that significantly impairs quality of life and mental health. Its pathogenesis remains incompletely understood. High-resolution impedance manometry provides the most reliable diagnostic approach at this moment. Botulinum toxin injection into the cricopharyngeus muscle is currently the most effective treatment, offering rapid and often long-term symptom relief, with in-office or endoscopic approaches demonstrating comparable results. Further research is needed to refine diagnostics, optimize treatment protocols, and clarify long-term outcomes.